Sarcopenia increases the risk of early biliary infection after percutaneous transhepatic biliary stent placement - Chen, Qi; Lu, Xun; Wang, Zhong-kai; Feng, Cheng; Yao, Xi-Juan; Guo, Jin-He (Frontiers in Oncology, 2022)
Purpose To assess the association between sarcopenia and the risk of early biliary infection (EBI) after percutaneous transhepatic biliary stent (PTBS) placement in patients with inoperable biliary tract cancer (BTC). Patients and Methods In this single center, retrospective observational study, patients diagnosed with inoperable BTC undergoing PTBS placement between January 2013 and July 2021 were enrolled. Preoperative sarcopenia was defined based on skeletal muscle mass measured by computed tomography images on the level of third lumbar vertebra within one month before PTBS placement. Patients were divided into two groups in accordance with the status of sarcopenia. Univariate and further multivariate logistic analyses were performed to determine predictors for EBI. Stratified and interactive analyses were conducted to investigate the stability of results. Further receiver operating characteristic curve was performed to determine the predictive value of sarcopenia on EBI after PTBS placement. Results Totally, 134 patients were included in this retrospective study, with 45 (33.6%) patients characterized as sarcopenia. The incidence rate of EBI was 26.9% (36/134). Multivariate analyses demonstrated that sarcopenia [Odds ratio (OR), 2.75; 95%CI: 1.11–6.77; P=0.028], obstruction length (OR, 1.04; 95%CI: 1.00–1.08; P=0.030) and diabetes (OR, 2.46; 95%CI: 1.01–5.96; P=0.047) were significant predictors of EBI. There were no significant interactions in different subgroups (P for interaction > 0.05). Moreover, the areas under the curves (AUC) revealed that the combined index containing sarcopenia, obstruction length, and diabetes showed the better predictive value (AUC= 0.723) than either one alone. Conclusion Sarcopenia increased the risk of EBI in patients with inoperable BTC after PTBS placement. Preoperative assessment of sarcopenia may aid in risk stratification. Patients with sarcopenia should be given intensive monitoring.